Audit fee trends from 2000 to 2014. Issue 1 (15th May 2018) - Dey, R. Mithu; Lim, Lucy
Abstract : Purpose: Setting audit fees is a persistent source of stress for auditors who must, on one hand, comply with the increasing government regulations that generally cause costs to rise; and on the other hand, respond to client pressures to keep audit fees down. In the post-scandal environment of Enron, WorldCom, and the demise of Arthur Andersen, policy makers have introduced additional costs for auditors by increasing regulations and creating a new industry watchdog – the Public Company Accounting Oversight Board (PCAOB). In this environment of constant pricing-cost tension for the auditor, the purpose of this paper is to examine audit fee trends over an extended period, 2000-2014. Design/methodology/approach: The authors calculate the unexpected audit fees using the audit fee model. The authors examine audit fee trends while controlling for changes due to inflation, auditor wages, and other audit fee determinants. Findings: The key findings indicate that audit fees increased in response to the promulgation of new audit regulations requiring additional audit work, the Sarbanes-Oxley (SOX) Act of 2002 and Auditing Standard No. 2 in 2004. Additionally, the authors find that audit fees decreased after new regulations alleviating audit work, namely the passage of Auditing Standard No. 5 in 2007, and remained unchanged when new regulations had a minimal impact on audit work, namely the Dodd-Frank Act of 2010. Practical implications: The findings of this research are relevant to audit clients, auditors, and regulators as they weigh the cost and benefits of significant new audit regulations and their impacts on audit fees. Originality/value: Using the more recent US data, the results in this paper show how events changed audit fee trends in recent years. The findings indicate that audit fees increased after the passage of new audit regulations such as the SOX Act of 2002, Auditing Standards No. 2 in 2004, and decreased after the passage of Auditing Standards No. 5 in 2007.